Hubungan Sindroma Down dengan Umur Ibu, Pendidikan Ibu, Pendapatan Keluarga, dan Faktor Lingkungan - Situmorang, Charina (Jurnal Kedokteran Indonesia, 2011)
Background. Maternal age is the main known risk factor of Down syndrome. Recently some researchershave suggested that there may be certain environmental factors that increase the risk of thecondition. This study aimed to estimate the association of Down syndrome and maternal age whilecontrolling for maternal education, family income and environmental factors.Methods. This study was analytic-observational using case control approach. It was conducted at aspecial school for children with disability in Surakarta. A sample of 20 mothers of children with DownSyndrome and 40 mothers of normal children, was selected by fixed-disease sampling. The relationshipbetween maternal age and the risk of Down syndrome while controlling for maternal education,family income, and environmental factor, was analyzed using multiple logistic logistic regression.Odds ratio was used to measure the association of variables.Results. Mean maternal age (year) at birth of Down syndrome children (37.82) was higher than that ofnormal children (28.60), and it was statistically significant. After controlling for maternal education,family income and living environmental factor, mothers aged 35 years or older had 12 times as manyrisk of Down syndrome as those aged less than 35 years, and it was statistically significant (OR= 12.10;95%CI 2.96 to 49.22). Evidence from this study did not support the relationship between maternaleducation, family income, and the risk of Down syndrome. Living in an unhealthy environment increasesthe risk of Down syndrome 2.5 times as many than living in a healthy environment, although thisrelationship was not statistically significant with the available sample size of 60 subjects (OR= 2.34;95%CI 0.44 to 15.28).Conclusion. There is a very strong relationship between maternal age at birth and the risk of deliveringchildren with Down syndrome, even after controlling for some potential confounding factors.Environmental factor seems to play a role in the incidence of this condition, but further studies areneeded with larger sample size.Key words: Down syndrome, maternal age, maternal education, family income, environmental factor